Improving The Economic Capability Of The Village Community Through Msme Karanggeneng Makmur, Sleman, Yogyakarta - Sunyoto, Danang; Kalijaga, Magister Alfatah; Hadi, Syamsul (SMARTINDO, 2023)
Objective:Efforts to improve the community's economy through MSME food product activities. Problems: Implementation of activities has not used methods according to marketing/sales theories. Method: Literature review and observation of activity implementation. Results: The implementation of MSME activities requires five methods in managing MSME so that they can be sustainable, namely the limited promotion method, direct sale, one seller one table, different product, limited time.